153 Anticoagulants and antiplatelets in COVID-19: impact on survival and thromboembolism development. (4th June 2021) - Salmon, Thomas; Titley, Mitchell; Noori, Zaid; Crosby, Mark; Sankaranarayanan, Rajiv
Abstract : Introduction: Higher rates of venous and arterial thromboembolism have been noted in coronavirus disease-2019 (COVID-19). There has been limited research on the impact of anticoagulant and antiplatelet choice in COVID-19. We performed a single-centre retrospective cohort study of 933 patients with confirmed COVID-19 infection, investigating the impact of anticoagulation and antiplatelet medication choice on survival and thromboembolism development. Methods: This was a single-centre retrospective cohort study of 933 patients with COVID-19 infection presenting between 01/02/2020 and 31/05/2020. Survival time at 90 days post-diagnosis and thromboembolism development were the measured outcomes. Patients were grouped by anticoagulant use on first presentation (direct oral anticoagulant, warfarin, therapeutic low molecular weight heparin, and no anticoagulation) and antiplatelet use on admission (aspirin, clopidogrel, dual antiplatelet therapy, or no antiplatelet therapy). Information on pre-existing cardiovascular disease and thromboembolism risk factors was also collected to adjust for confounding variables. Statistical analysis was performed using SPSS version 27.0.1.0. Results: Of 933 total patients, mean age was 68 years and 54.4% were male. 297 (31.8%) did not survive at 90 days. A Cox proportional hazards model analysis found no statistically significant relationship between anticoagulant or antiplatelet choice and survival (p<0.05). 57 (6.3%) developed thromboembolism. Antiplatelet choice was not shown to have a statistically significant relationship with thromboembolism development. Warfarin and direct oral anticoagulant (DOAC) use did not have a statistically significant impact on thromboembolism development (p<0.05). Therapeutic low molecular weight heparin (LMWH) use was associated with increased thromboembolism risk (Odds ratio = 14.327, 95% CI 1.904 – 107.811, p = 0.010).Additionally, neither ischaemic heart disease, heart failure, or arrhythmia history were found to be associated with decreased survival at 90 days or increased thromboembolism development. Conclusions: Antiplatelet choice was shown to have no impact on survival or thromboembolism development in COVID-19. No patient on dual antiplatelet therapy developed thromboembolism, but this was not found to be statistically significant in multivariate analysis and the sample size was limited (n=7). Anticoagulant choice did not impact survival or thromboembolism development, aside from LMWH. Therapeutic LMWH use was associated with increased risk of thromboembolism. Again, it should be noted that the sample size for patients using therapeutic LMWH was small (n=4), and there may be confounding variables affecting both LMWH use and thromboembolism development. The findings relating to the impact of dual antiplatelet therapy and therapeutic LMWH use on thromboembolism development in COVID-19 should be repeated with a larger sample size and additional adjustment for cofounding variables. Conflict of Interest: The authors have no competing interests to declare